Ischemic preconditioning affects phosphosites and accentuates myocardial stunning while reducing infarction size in rats - Elmahdy, Ahmed; Shekka Espinosa, Aaron; Kakaei, Yalda; Pylova, Tetiana; Jha, Abhishek; Zulfaj, Ermir; Krasnikova, Maryna; Al-Awar, Amin; Sheybani, Zahra; Sevastianova, Valentyna; Berger, Evelin; Nejat, Amirali; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background and aims: Ischemic preconditioning (IPC), i.e., brief periods of ischemia, protect the heart from subsequent prolonged ischemic injury, and reduces infarction size. Myocardial stunning refers to transient loss of contractility in the heart after myocardial ischemia that recovers without permanent damage. The relationship between IPC and myocardial stunning remains incompletely understood. This study aimed primarily to examine the effects of IPC on the relationship between ischemia duration, stunning, and infarct size in an ischemiareperfusion injury model. Secondarily, this study aimed to examine to which extent the phosphoproteomic changes induced by IPC relate to myocardial contractile function.Methods and results: Rats were subjected to different durations of left anterior descending artery (LAD) occlusion, with or without preceding IPC. Echocardiograms were acquired to assess cardiac contraction in the affected myocardial segment. Infarction size was evaluated using triphenyl tetrazolium chloride staining.Phosphoproteomic analysis was performed in heart tissue from preconditioned and non-preconditioned animals.In contrast to rats without IPC, reversible akinesia was observed in a majority of the rats that were subjected to IPC and subsequently exposed to ischemia of 13.5 or 15 minutes of ischemia. Phosphoproteomic analysis revealed significant differential regulation of 786 phosphopeptides between IPC and non-IPC groups, with significant associations with the sarcomere, Z-disc, and actin binding.IPC preferentially induces changes in phosphosites of proteins involved in myocardial contraction, and both associates with increased extent of reversible post-ischemic myocardial stunning after ischemiareperfusion injury and reduces infarction size.